What's 'SUP' with paddlers? Integrating spatial, social, and ecological data to understand behavior among paddlesport users at a popular lake destination. (October 2021) - Baker, Jenna; D'Antonio, Ashley; Monz, Christopher; Taff, Derrick; Rice, William L.; Newton, Jennifer; Newman, Peter; Miller, Zachary D.; Freeman, Stephanie
Abstract: Non-motorized, water-based recreation (e.g., paddlesports) represents one of the most sought after outdoor activities in U.S. Parks and Protected Areas (PPA). Among paddling options, stand-up paddleboarding represents the activity with the highest levels of growth. However, stand-up paddleboarding has yet to be spatially examined in a PPA setting. This research paired GPS-tracking data of paddlesport users with corresponding social and environmental information to build a robust understanding of paddlesport behavior and experience in PPA. Statistical classification procedures revealed distinctions in movement across paddling activity types, highlighting implications for resource protection and visitor flow management. Integrating spatial and non-spatial data identified numerous drivers and impacts of paddlesport use: the motivation to escape corresponded to traveling further distances, while higher group sizes and prolonged shoreline exposure aligned with concentrated use levels near parking lots and facilities. Results broaden our knowledge of recreationist movement and experience, and add to a growing body of PPA research that incorporates mixed method spatial approaches to research designs. Furthermore, these findings contribute novel information on paddlesport spatial behavior in PPAs, especially given the emergent introduction of stand-up paddleboarding. Highlights: Paddling activity type had an effect on spatiotemporal behaviors. Despite options to disperse, the majority of paddler movement concentrated near parking lots and denuded shorelines. The temporal use of space varied across user groups highlighting distinctions in space-time budgets. Paddlers with social motivations did not travel as far as those motivated to escape. The level of contact with shoreline impacts differed across paddler activity types.